Butaro Hospital, a Sustainable Hospital with Participatory Design and Construction Process - Gunawan Tanuwidjaja; Ellen Yih-Jing Huang; Ilena Hadi Sutanto; Antonius Archie Tobias; Chen Ce Siong; Jesslyn Bahtiar; Yohanes Richo Wirawan (RUAS (Review of Urbanism and Architectural Studies), 2016)
Healthcare facilities are very important for sustainable rural regions in developing countries. The Republic of Rwanda, in central east Africa, suffered massive social conflict in 1994 between the Hutu and Tutsi. Furthermore the health problem happened in Burera District because of lack of a proper district hospital. Therefore, in January 2011, the Rwandan Ministry of Health and Partners in Health (PIH) opened the 140-bed Butaro Hospital in the Burera District of Rwanda. The paper-based research was conducted based on hospital’s architecture of Hatmoko, et.al. (2010). Analysis was made with based on the secondary data of Butaro Hospital. Lastly, primary data gathering would be conducted if the funding allowed. The Butaro Hospital was an affordable solution for healthcare problems in rural regions of the developing countries, especially the infectious diseases (such as: HIV, malaria, tuberculosis, nose-ear-and-throat disease). Sustainable innovative solutions for minimum infection were implemented such as: external corridors, large-radius-low-speed fans (with diameters of 24 feet), high-louvered windows, germicidal UV lights, and non-permeable-continuous flooring. The construction of the hospital also would reduce the impact of political crisis in 1994. The project created 4,000 jobs for local craftsmen and local residents. They were initially trained for manual excavation, construction, and project management, before involving in the hospital construction. Therefore, the Butaro Hospital supported the smart regions of Burera area.Keywords: Sustainable and affordable hospital, participatory design, local material